Analisis Desain Kurikulum Mata Pelajaran PAI di SMPN 13 Tais Seluma - Een Suparmanto (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Curriculum development design is a composition or design of a curriculum model designed in accordance with the vision and mission of the school which in its development goes through a process of validation, implementation and evaluation. This research is motivated by the practice of PAI in schools which is less than optimal, especially due to the lack of teaching hours. Seeing this problem, the development of the PAI curriculum becomes very important to be carried out, both by related institutions and by PAI teachers themselves. The purpose of this study is to find out and analyze: development of PAI objectives, development of PAI substance, development of PAI implementation, and development of PAI evaluation. This study uses a case study method using a qualitative approach. Data collection techniques are carried out by means of interviews, observations and documentation studies. Based on the results of the study, it was found that the development of PAI objectives is to develop academic abilities and prioritize Islamic character values in students. The development of PAI substance is developed into two forms, namely intracurricular forms, in the form of Tarjamah subjects and school culture forms (school habits) in the form of Tahfiz and Taqwa Character Building (TCB). The development of evaluation of the PAI curriculum is carried out in two activities, namely evaluation by each school unit of SMP Negeri 13 Tais Seluma.